THE URGENCY OF CONSUMER PROTECTION LEGAL REFORM IN LIVE SHOPPING TRANSACTIONS IN INDONESIA - Sofyan Jafar; Muhibuddin; Zulkifli; Teuku Yudi Afrizal; Nasrianti (PT. Radja Intercontinental Publishing, 2024)
The development of digital technology has driven the emergence of a new live-streaming, or live shopping, trading model on e-commerce platforms and social media in Indonesia. This trading system allows businesses to promote products interactively and in real time to consumers. While offering convenience in digital transactions, live shopping also raises various legal issues that have the potential to harm consumers, such as product information manipulation, goods that do not conform to promotions, digital fraud, the use of detrimental standard clauses, and the misuse of consumers' personal data. These conditions indicate that consumers remain in a weak position in modern digital commerce practices. This study aims to analyze the effectiveness of legal protection for consumers in live shopping transactions in Indonesia and to evaluate the weaknesses of consumer protection regulations in addressing the development of live-streaming-based digital commerce. The study uses a normative legal research method with a statutory, conceptual, and case-based approach. Legal materials were obtained through a literature review consisting of primary, secondary, and tertiary legal materials. The results indicate that legal protection for consumers in live shopping practices is not yet effective. Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Information and Electronic Transactions do not specifically regulate live shopping-based trade mechanisms. Furthermore, weak oversight of digital platforms, low public legal literacy, and suboptimal digital dispute resolution mechanisms mean that consumer legal protection remains normative and unable to provide maximum legal certainty. The novelty of this research lies in its specific analysis of the effectiveness of consumer legal protection in live shopping practices, a rapidly growing modern digital commerce model in Indonesia. This research also emphasizes the urgency of digital regulatory reforms that are more adaptive to technological developments and e-commerce activities.